Site-Randomized Controlled Trial of a Combined Cognitive Behavioral Therapy and a Medication Management Algorithm for Treatment of Depression Among Youth Living With HIV in the United States. (15th December 2021) - Brown, Larry K.; Chernoff, Miriam; Kennard, Betsy D.; Emslie, Graham J.; Lypen, Kathryn; Buisson, Sarah; Weinberg, Adriana; Whiteley, Laura B.; Traite, Shirley; Krotje, Chelsea; Harriff, Lauren; Townley, Ellen; et al.
Abstract : Background: Depression is frequent among youth living with HIV (YLWH). Studies suggest that manualized treatment guided by symptom measurement is more efficacious than usual care. Setting: This study evaluated manualized, measurement-guided depression treatment among YLWH, aged 12–24 years at 13 US sites of the International Maternal Pediatric Adolescent AIDS Clinical Trials Network. Methods: Using restricted randomization, sites were assigned to either a 24-week, combination cognitive behavioral therapy and medication management algorithm (COMB-R) tailored for YLWH or to enhanced standard of care, which provided standard psychotherapy and medication management. Eligibility included diagnosis of nonpsychotic depression and current depressive symptoms. Arm comparisons used t tests on site-level means. Results: Thirteen sites enrolled 156 YLWH, with a median of 13 participants per site (range 2–16). At baseline, there were no significant differences between arms on demographic factors, severity of depression, or HIV status. The average site-level participant characteristics were as follows: mean age of 21 years, 45% male, 61% Black, and 53% acquired HIV through perinatal transmission. At week 24, youth at COMB-R sites, compared with enhanced standard of care sites, reported significantly fewer depressive symptoms on the Quick Inventory for Depression Symptomatology Self-Report (QIDS-SR score 6.7 vs. 10.6, P = 0.01) and a greater proportion in remission (QIDS-SR score ⩽ 5; 47.9% vs. 17.0%, P = 0.01). The site mean HIV viral load and CD4 T-cell level were not significantly different between arms at week 24. Conclusions: A manualized, measurement-guided psychotherapy and medication management algorithm tailored for YLWH significantly reduced depressive symptoms compared with standard care at HIV clinics. Abstract : Supplemental Digital Content is Available in the Text.